“PENGARUH PEMAHAMAN DASAR AKUNTANSI, PENGETAHUAN KEWIRAUSAHAAN, E-COMMERCE, DAN MOTIVASI TERHADAP NIAT MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA” - Sandi Muhammad Akbar; Isma Coryanata (ITB AAS Indonesia Surakarta, 2024)
This research aims to examine the influence of basic accounting understanding, entrepreneurial knowledge, e-commerce, as well as motivation and interest in entrepreneurship among accounting students at the University of Bengkulu. In this study, the population used was 320 people with the criteria being students of the 7th and 5th semester accounting study program who had taken accounting introduction and entrepreneurship courses and using a non-probability sampling method based on the results of calculations using the Slovin formula, a research sample of 76 students was obtained. In this research, the method used is a quantitative method, SPSS 27 using in this research to testing hypotheses and processing data. The results of this research show that accounting understanding, entrepreneurial knowledge, e-commerce, motivation have a simultaneously affect interest in entrepreneurship among accounting students at the University of Bengkulu .